2015
DOI: 10.1371/journal.pone.0122351
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Iron Ion on the Specificity of Photodynamic Therapy with 5-Aminolevulinic Acid

Abstract: Recently, photodynamic therapy using 5-aminolevulinic acid (ALA-PDT) has been widely used in cancer therapy. ALA administration results in tumor-selective accumulation of the photosensitizer protoporphyrin IX (PpIX) via the heme biosynthetic pathway. Although ALA-PDT has selectivity for tumor cells, PpIX is accumulated into cultured normal cells to a small extent, causing side effects. The mechanism of tumor-selective PpIX accumulation is not well understood. The purpose of the present study was to identify th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 25 publications
1
16
0
1
Order By: Relevance
“…Iron is the substrate for conversion of PpIX to heme, and Hayashi et al . found that uptake abilities of iron into mitochondria play an important role in tumor-selective PpIX accumulation 51 . Therefore, reduced amounts of iron in mitochondria by DFO may lead to enhanced PpIX accumulation in SP-defined GSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Iron is the substrate for conversion of PpIX to heme, and Hayashi et al . found that uptake abilities of iron into mitochondria play an important role in tumor-selective PpIX accumulation 51 . Therefore, reduced amounts of iron in mitochondria by DFO may lead to enhanced PpIX accumulation in SP-defined GSCs.…”
Section: Discussionmentioning
confidence: 99%
“…48 Breast cancer cells (MCF7) were reported to have lower levels of mitochondrial labile iron compared with healthy epithelial cells (MCF10A). 30 In the presence of excess iron, PpIX levels dropped in the cancer cells (although they were still higher than in healthy cells), suggesting that impaired uptake of iron might be a factor in PpIX accumulation. Supporting this observation, these cancer cells expressed lower levels of mRNA for the mitochondrial iron transporters, mitoferrin-1 and mitoferrin-2.…”
Section: Role Of Iron In Ferrochelatase Regulation In Cancermentioning
confidence: 96%
“…In the human body, 5-ALA is synthesized to protoporphyrin IX (PpIX) in the mitochondria, and divalent iron ion is inserted into PpIX to form heme. Hayashi et al showed that the usage of SFC as a form of iron enhanced the specific effect of 5-ALA in tumor PDT [ 96 ].…”
Section: Novel Strategies For Preventing Fatty Liver Ir Injury Using mentioning
confidence: 99%